Mitigation of Voltage Sag and Swell Using Battery Based Dynamic Voltage Restorer: A Detailed Study - Bangarraju, J.; Jayalaxmi, A.; Rajagopal, V. (Innovations in Science and Technology Vol. 1, 2021)
The use of a battery-based dynamic voltage restorer (DVR) to mitigate voltage sag and swell is described in this work. The DVR is a three-phase controlled voltage source with a magnitude of voltage and angle that adds/subtracts from the source voltage during sag/swell. The DVR can inject a voltage of the desired magnitude and phase at fundamental frequency in each phase. Within milliseconds, the DVR can restore the load voltage. Voltage sag and voltage swell problems can be solved quickly and efficiently with DVR. Synchronous Reference Frame Theory (SRFT) is used to estimate reference voltages, and gate pulses are created by monitoring the source, load terminal voltages, and supply currents. Utilizing MATLAB/ SIMULINK and the power system Block set (PSB) toolboxes, the mitigation of voltage sag and swell using SRFT for battery-based DVR is simulated.